2022
DOI: 10.3389/fpsyg.2022.987060
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the past and the future: Academic geographical (im)mobility of Chinese women academics throughout doctoral education

Abstract: IntroductionAcademic geographical mobility is considered to be critical to academic excellence, but it is a gendered terrain. This study seeks to examine the career progression of Chinese women academics, as shaped by gender norms, regarding academic geographical (im)mobility throughout their doctoral education, in retrospect.MethodsTo address this issue, driven by the Butlerian theoretical concept of “a stylized repetition of acts,” the present study analyzed the qualitative data from semi-structured intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Contemporary research conducted in higher education context in China has predominantly focused on exploring the factors that influence the intention to pursue higher education ( Dai et al, 2021 ) or on analyzing the status of gendered education ( Wang and Stocker, 2010 ; Si, 2022 ). A previous study identified gender norms as a contributor to the geographical immobility of Chinese women academics ( Bao, 2022 ) and another study analyzed factors that prevent girls and women from pursuing a scientific career in Taiwan ( Cheng, 2010 ). However, only a few studies from Taiwan have employed a qualitative approach, in which academic scientists in medical sciences were encouraged to share their experiences of working in laboratory settings.…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary research conducted in higher education context in China has predominantly focused on exploring the factors that influence the intention to pursue higher education ( Dai et al, 2021 ) or on analyzing the status of gendered education ( Wang and Stocker, 2010 ; Si, 2022 ). A previous study identified gender norms as a contributor to the geographical immobility of Chinese women academics ( Bao, 2022 ) and another study analyzed factors that prevent girls and women from pursuing a scientific career in Taiwan ( Cheng, 2010 ). However, only a few studies from Taiwan have employed a qualitative approach, in which academic scientists in medical sciences were encouraged to share their experiences of working in laboratory settings.…”
Section: Introductionmentioning
confidence: 99%